2020
DOI: 10.3310/hsdr08180
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-based interventions to promote healthy lifestyles in the NHS workforce: a rapid scoping and evidence map

Abstract: Background The health and well-being of staff working in the NHS is a significant issue for UK health care. We sought to identify research relevant to the promotion of healthy lifestyles among NHS staff on behalf of NHS England. Objectives To map existing reviews on workplace-based interventions to promote health and well-being, and to assess the scope for further evidence synthesis work. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…We found that wellness programs vary widely in format. In agreement with our findings, a scoping review found disparate focus, interventions, and outcomes, with most evaluating effectiveness and few reporting on costs or implementation challenges [28]. One robust review found strong evidence for workplace interventions targeting physical activity and diet to improve weight-related outcomes, the use of psychological interventions (especially e-health and cognitive behavioral therapy) to prevent mental health disorders, and resistance exercise training in the prevention of musculoskeletal disorders.…”
Section: Multicomponent Wellness Programssupporting
confidence: 85%
“…We found that wellness programs vary widely in format. In agreement with our findings, a scoping review found disparate focus, interventions, and outcomes, with most evaluating effectiveness and few reporting on costs or implementation challenges [28]. One robust review found strong evidence for workplace interventions targeting physical activity and diet to improve weight-related outcomes, the use of psychological interventions (especially e-health and cognitive behavioral therapy) to prevent mental health disorders, and resistance exercise training in the prevention of musculoskeletal disorders.…”
Section: Multicomponent Wellness Programssupporting
confidence: 85%
“…The benefits of healthy behaviours acquired at work may spill into daily life and continue into later life. Workplace interventions have been the subject of a large literature, which was compiled in a recent overview [ 5 ]. However, very few studies have examined the effects of monetary incentives targeted at organisations despite use of monetary incentives by both the US and UK governments.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the search for strategies to increase work engagement and reduce burnout and occupational stress [ 25 , 26 ] has been the main objective. The close relationship between occupational stress and sleep disturbances [ 27 ] and between workplace violence and stress [ 28 ] has led to a project designed to promote sleep quality [ 29 ] and another for encouraging nonviolent behaviors [ 30 ]. Aging and its consequent effect on working attitudes [ 31 , 32 ] prompted another project, supported by a comparison with European experiences in the framework of an international collaboration [ 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%